Molecular regulation of the cardiac-enriched acetyl-CoA carboxylase isoform (ACCβ) : a novel target for therapeutic interventions in cardiovascular disease - Makaula, Siyanda S S (Department of Medicine, 2014)
Includes bibliographical references (leaves 130-173).